Method for manufacturing a composite, composite, composition for forming a porous layer, and porous layer
Patent Information
- Application Number
- JP2025064549
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-09
- Publication Date
- 2026-10-22
AI Technical Summary
【0010】 環境負荷が低く、且つ、簡便で、2つの部材間で十分な接合強度が得られる接合方法、及び、当該接合方法を含む複合体の製造方法を提供する。
Smart Images

Figure 2026170762000001_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present invention relates to a method for producing a composite, a composite, a composition for forming a porous layer, and a porous layer.
BACKGROUND ART
[0002] As a method for joining two members, adhesives are generally widely used. However, since adhesives need to be compatible (have affinity) with both materials to be joined, it has not been easy to strongly join dissimilar materials having different properties.
[0003] As a joining technique for dissimilar materials, a physical joining method is known in which irregularities called anchors are formed on the joining surface. Examples of the anchor forming method include mechanical cutting, laser processing, chemical etching and the like. For example, as a technique for enhancing the joining strength between a metal member and a resin member, methods of forming an anchor on a metal surface by chemical etching have been proposed by various companies (for example, Chemiblast (registered trademark) of Nihon Parkerizing Co., Ltd., AMALPHA (registered trademark) of MEC Co., Ltd., NAT (Nano Adhesion Technology) and NMT (Nano Molding Technology) of Taisei Plus Co., Ltd.).
[0004] Further, Patent Document 1 discloses a method of providing a porous adhesive layer between two members. A porous layer is formed by applying an epoxy resin or the like containing a pore-forming agent (porogen) onto a first substrate, and removing the pore-forming agent. By forming a second substrate on this porous layer, the joining strength is improved by the anchor effect.
PRIOR ART DOCUMENTS
PATENT DOCUMENTS
[0005]
PATENT DOCUMENT 1
SUMMARY OF THE INVENTION
PROBLEMS TO BE SOLVED BY THE INVENTION
[0006] However, conventional bonding methods utilizing the anchoring effect have the following problems: Anchor formation by mechanical cutting, etc., generates residue, requiring cleaning, and this residue may cause variations in bonding strength. Furthermore, anchor formation by laser processing is difficult to create connecting holes or more complex mesh-like or labyrinthine uneven structures, and there is a risk that sufficient adhesive strength cannot be obtained. Furthermore, anchor formation by chemical etching uses strong acids and also discharges dissolved (ionized) metals, resulting in a high environmental burden. The method described in Patent Document 1 has a low environmental burden, but it generates residue, and because the formed pore diameter is large, there is a risk that sufficient bonding strength cannot be obtained. In addition, since the pore-forming agent (pologen) has poor solvent properties with respect to the resin (epoxy resin, etc.) that forms the porous layer, the resin solution for forming the porous layer in Patent Document 1 is unstable and may have low storage stability.
[0007] The present invention solves the above problems. Specifically, the present invention provides a joining method that has a low environmental impact, is simple, and provides sufficient bonding strength between two members, and a method for manufacturing a composite including the joining method. [Means for solving the problem]
[0008] As a result of diligent research to achieve the above objectives, the inventors of this invention have found that the above objectives can be achieved with the following configuration.
[0009] [1] A method for manufacturing a composite including a joined first member and a second member, A porous layer-forming composition is applied to the surface of the first member to form a coating layer, By vaporizing and removing the mixed solvent from the coating layer at a temperature of 5°C or higher, a porous layer is formed. Applying a liquid composition onto the porous layer, This includes solidifying the liquid composition to form a second member, The porous layer forming composition is The mixed solvent containing two or more organic solvents, The mixture includes a polymer for porous layers dissolved in the aforementioned mixed solvent, The aforementioned mixed solvent is Of the aforementioned organic solvents, the second organic solvent with the highest boiling point, A method for producing a composite, comprising a first organic solvent having a boiling point 20°C to 150°C lower than the boiling point of a second organic solvent. [2] The method for producing the composite according to [1], wherein the concentration of the porous layer polymer in the porous layer forming composition is 1% by mass to 35% by mass. [3] In the porous layer forming composition, A method for producing a composite according to [1] or [2], wherein the ratio (V1 / V2) of the volume of the first organic solvent (V1) to the volume of the second organic solvent (V2) is 50 / 50 or more. [4] A method for producing a composite according to any one of [1] to [3], wherein the polymer for the porous layer comprises at least one selected from the group consisting of acrylic resin, vinyl copolymer of polyolefin resin, fluororesin, polyamic acid, and polysilazane. [5] A method for producing a composite according to any one of [1] to [4], wherein a phase separation occurs between the porous layer polymer and the mixed solvent in the process of vaporizing and removing the mixed solvent from the coated layer. [6] A method for producing a composite according to any one of [1] to [5], wherein, by applying the liquid composition, at least a portion of the liquid composition impregnates the porous layer, and the second member is formed continuously from the inside of the porous layer. [7] A complex, First member and A porous layer formed on the surface of the first member, It comprises a second member formed on the porous layer, The second member is a composite in which a portion of it penetrates the porous layer and is formed continuously from the interior of the porous layer. [8] A porous layer forming composition used for joining a first member and a second member, A mixed solvent containing two or more organic solvents, a polymer for a porous layer dissolved in the mixed solvent, The mixed solvent comprises: a second organic solvent having the highest boiling point among the organic solvents, and a first organic solvent having a boiling point 20°C to 150°C lower than the boiling point of the second organic solvent, the composition for forming a porous layer. [9] A porous layer for bonding a first member and a second member, comprising at least one selected from the group consisting of acrylic resins, vinyl copolymers of polyolefin resins, fluororesins, polyimides, and silica glass, with a thickness of 50 nm to 100 μm, and an average pore size of 1 nm to 100 μm or less, the porous layer. [Effects of the Invention]
[0010] Provided are a bonding method that has low environmental impact, is simple, and can achieve sufficient bonding strength between two members, and a method for producing a composite including the bonding method. [Brief Description of the Drawings]
[0011] [Figure 1] This is a flowchart illustrating the method for producing a composite in the embodiment. [Figure 2] Figure 2(a) is a schematic cross-sectional view of the porous layer formed on the first member described in the embodiment, Figure 2(b) is a schematic cross-sectional view of the composite described in the embodiment, and Figure 2(c) is a schematic cross-sectional view of the composite described in a modified example of the embodiment. [Figure 3] Figures 2(a) to (b) are atomic force microscope (AFM) photographs of Sample 1-1 and Sample 1-2 produced in the examples, respectively. [Figure 4] Figures 4(a) to (b) are atomic force microscope (AFM) photographs of Sample 2-1 and Sample 2-2 produced in the examples, respectively. [Figure 5] Figures 5(a) to (d) are atomic force microscope (AFM) photographs of Sample 3-1 to Sample 3-4 produced in the examples, respectively. [Figure 6]FIG. 6(a) is an atomic force microscope (AFM) photograph of Sample 3-5 produced in the Examples, and FIG. 6(b) is an optical microscope photograph of Sample 3-5 (a wide-area photograph of FIG. 6(a)). [Figure 7] FIGS. 7(a) to (c) are atomic force microscope (AFM) photographs of Sample 4-1 to Sample 4-3 produced in the Examples, respectively. [Figure 8] FIGS. 8(a) to (d) are atomic force microscope (AFM) photographs of Sample 5-1 to Sample 5-4 produced in the Examples, respectively. [Figure 9] FIGS. 9(a) to (c) are atomic force microscope (AFM) photographs of Sample 6-1 to Sample 6-3 produced in the Examples, respectively. [Figure 10] FIG. 10(a) is a cross-sectional scanning electron microscope (SEM) photograph showing a state where a porous layer is formed on a glass plate in Experiment 7 of the Examples. FIG. 10(b) is a cross-sectional SEM photograph of Sample 7 produced in the Examples. [Figure 11] It is a diagram showing the bonding strength evaluation results of Sample 7 produced in the Examples. [Figure 12] FIG. 12(a) is a schematic perspective view of Sample 8 produced in the Examples, and FIG. 12(b) is a diagram showing the bonding strength evaluation results of Sample 8. [MODE FOR CARRYING OUT THE INVENTION]
[0012] Hereinafter, embodiments of the present invention will be described in detail. The description of the constituent elements set forth below may be made based on representative embodiments of the present invention, but the present invention is not limited to such embodiments. In the present specification, a numerical range represented using "to" means a range including the numerical values stated before and after "to" as the lower limit value and the upper limit value. Further, in the present specification, "(meth)acryl" means methacryl and / or acryl, and "(meth)acryloyl" means acryloyl and / or methacryloyl.
[0013] The method for producing a composite body of the present embodiment includes the following steps. (Step S1) Apply a porous layer-forming composition to the surface of the first member to form a coating layer. (Step S2) A porous layer is formed by vaporizing and removing the mixed solvent from the coated layer at a temperature of 5°C or higher. (Step S3) Applying a liquid composition onto the porous layer, (Step S4) Solidify the liquid composition to form the second member.
[0014] In the manufacturing method of the composite of this embodiment (hereinafter referred to as "this manufacturing method"), two members (a first member and a second member) are joined by a porous layer. Conventional adhesives needed to have affinity with both members, but in this manufacturing method, the porous layer only needs to have affinity with one of the members (the first member). Since it is connected to the other member (the second member) by an anchoring effect, it is possible to join with a wider range of materials, such as dissimilar materials with different properties.
[0015] Furthermore, as will be described in detail later, the porous layer (anchor layer) of this manufacturing method can be formed by a very simple method of applying a porous layer-forming composition (polymer solution) of a specific composition to the first component and drying it (removal of the mixed solvent). This makes it possible to shorten the manufacturing time of the entire composite, improve efficiency, and reduce costs. Moreover, the formation of the porous layer in this manufacturing method does not generate any residue and has a lower environmental impact than chemical etching. In addition, compared to laser processing or methods using pore-forming agents (pologens) (for example, Patent Document 1), it is possible to form more complex porous shapes and smaller pore diameters, and the adhesive strength between components can be further improved. The details of this manufacturing method are described below.
[0016] <Process S1> A porous layer-forming composition is applied to the surface of the first member to form a coating layer (step S1 in Figure 1).
[0017] The porous layer-forming composition comprises a mixed solvent and a porous layer polymer dissolved in the mixed solvent. The porous layer polymer is either a polymer constituting the porous layer formed in step S2, or a precursor polymer of the polymer constituting the porous layer. The porous layer polymer is preferably an uncrosslinked polymer so as to be easily soluble in the mixed solvent. The porous layer polymer may be an organic polymer or an inorganic polymer.
[0018] While there are no particular limitations on the organic polymer, thermoplastic polymers are preferred because they are easily soluble in the mixed solvent. Examples include the following resins and copolymers thereof: acrylic resins, polyolefin resins, fluororesins, polyamic acid (polyamic acid) which is a precursor of polyimide resins, polyvinyl alcohol, polyvinyl chloride, polyacrylonitrile, polycarbonate, polyvinyl acetate, styrene-based resins (e.g., polystyrene, AS resin, ABS resin, etc.), polyamide resins (e.g., nylon, etc.), polyester resins (e.g., polyethylene terephthalate, polybutylene terephthalate, etc.), polyether ketones, polysulfones, polyoxymethylene, polyphenylene sulfide, cellulose resins, etc.
[0019] Examples of inorganic polymers, though not particularly limited, include polysilazanes (PHPS: perhydropolysilazanes), which are precursors of silica glass (silicon dioxide).
[0020] The polymer for the porous layer may consist of only one type of polymer, or it may contain two or more types of polymers, as long as the effects of this embodiment are achieved. Furthermore, if necessary, the polymer for the porous layer may contain known additives such as fillers.
[0021] In terms of being able to produce porous layers more efficiently and thereby increase bonding strength, the polymers for porous layers are preferably (i) acrylic resins, (ii) vinyl copolymers of polyolefin resins, (iii) fluororesins, (iv) polyamic acids (precursors of polyamic acid and polyimide), and (v) polysilazanes (precursors of silica glass).
[0022] (i) The acrylic resin is not particularly limited, but examples include (meth)acrylic acid resin, (meth)acrylic acid ester resin, and copolymers thereof. In (meth)acrylic acid ester resin, the hydrocarbon group (-R in -C(O)OR) bonded to the oxygen atom of the ester group is, for example, an alkyl group having 1 to 6 carbon atoms, and a methyl group is preferred.
[0023] (ii) Polyolefins are olefins (alkenes, C n H 2n Polyolefin resins are polymers formed by the polymerization of polyolefins, and examples include polyethylene, polypropylene, polybutene, etc., and copolymers thereof. A vinyl copolymer of polyolefin resins is a copolymer of a polyolefin monomer and a monomer having a vinyl group (CH2=CH-) or a vinylidene group (CH2=C<). Examples of vinyl copolymers of polyolefin resins include ethylene / vinyl alcohol copolymer, ethylene / vinyl acetate copolymer, ethylene / vinyl chloride copolymer, ethylene / acrylic acid ester copolymer, ethylene / propylene copolymer, etc., and among these, ethylene-vinyl alcohol copolymer (PVA-co-PE) is preferred.
[0024] (iii) Examples of fluororesins include polyvinylidene fluoride, poly(hexafluoropropylene), poly(trifluoroethylene), and copolymers thereof, among which (vinylidene fluoride / hexafluoropropylene) copolymer (P(VDF-HFP)) and (vinylidene fluoride / trifluoroethylene) copolymer (P(VDF-TrFE)) are preferred.
[0025] The molecular weight of the polymer for the porous layer is not particularly limited and may be appropriately selected depending on the type of polymer, etc.
[0026] The concentration of the porous layer polymer in the porous layer forming composition may be, for example, 1% to 35% by mass, preferably 3% to 18% by mass. By setting the concentration of the porous layer polymer within the above range, a porous layer can be produced more efficiently, and as a result, the bonding strength can be increased.
[0027] The polymer for forming the porous layer is dissolved in the mixed solvent. By using such a stable porous layer-forming composition, a uniform porous layer can be produced more efficiently, and the storage stability of the porous layer-forming composition is also improved. "Dissolved" in the mixed solvent means that no precipitates of the porous layer polymer can be observed when the porous layer-forming composition is visually inspected.
[0028] The mixed solvent in the porous layer-forming composition contains two or more organic solvents. The number of organic solvents is not particularly limited as long as there are two or more, but for example, it may be five or fewer, preferably two or three. The mixed solvent contains a second organic solvent with the highest boiling point among the contained organic solvents, and a first organic solvent having a boiling point 20°C to 150°C lower than the boiling point of the second organic solvent. In this specification, boiling point means the boiling point at atmospheric pressure (1 atm = 0.10 MPa).
[0029] The second organic solvent is not particularly limited, but may be appropriately selected from solvents with boiling points of 70°C to 300°C, for example. The boiling point of the second organic solvent may be, for example, 75°C to 250°C, 70°C to 150°C, or 200°C to 300°C. The boiling point of the first organic solvent is not particularly limited as long as there is a predetermined temperature difference between it and the first organic solvent. For example, it may be appropriately selected from solvents with boiling points of 50°C to 250°C. The boiling point of the first organic solvent may be, for example, 50°C to 100°C, 70°C to 150°C, or 150°C to 250°C. Furthermore, the first solvent may consist of one type of solvent or two or more types of solvents.
[0030] In step S2, described later, the mixed solvent containing a first organic solvent and a second organic solvent with different boiling points vaporizes from the coated layer in multiple stages (starting with the lower boiling point solvent), and in this process, phase separation (drying-induced phase separation) occurs between the polymer for the porous layer and the solvent. As a result, as shown in Figure 2(a), after the mixed solvent vaporizes, a porous layer 70 is formed on the first member 10. In terms of efficiently forming a porous layer, it is preferable that both the first organic solvent and the second organic solvent are volatile organic solvents that vaporize easily at room temperature and pressure. Furthermore, it is preferable that the first organic solvent and the second organic solvent are miscible without separation (forming a homogeneous phase).
[0031] In terms of the ease with which the porous layer polymer dissolves in the mixed solvent, either one or both of the first and second organic solvents may be good solvents for the porous layer polymer. Alternatively, either one or both of the first and second organic solvents may be poor solvents (not soluble or have very low solubility) for the porous layer polymer. If the porous layer polymer cannot be sufficiently dissolved by the first and second organic solvents alone, other solvents may be added to the mixed solvent to improve the solubility of the porous layer polymer. The other solvents may be, for example, water or an organic solvent (third organic solvent), and may be appropriately selected depending on the type of porous layer polymer. The solubility (solubility) of the porous layer polymer in each solvent may be higher in the first organic solvent or higher in the second organic solvent, but it is preferable that the solubility in the first organic solvent is higher.
[0032] The types of the first and second organic solvents may be appropriately selected depending on the type of polymer used for the porous layer. Below are preferred examples of the first and second organic solvents that facilitate the formation of a porous layer more efficiently.
[0033] When the polymer for the porous layer is (i) an acrylic resin, examples of the first organic solvent include acetone (boiling point: 56°C), chloroform (boiling point: 61.2°C), ethyl acetate (boiling point: 77.1°C), and benzene (boiling point: 80.1°C), and examples of the second organic solvent include ethanol (boiling point: 78.4°C), benzene, and toluene (boiling point: 110.6°C).
[0034] When the polymer for the porous layer is (ii) a vinyl copolymer of polyolefin resin, the first organic solvent may be methanol (boiling point: 64.7°C), ethanol (boiling point: 78.4°C), isopropyl alcohol (IPA, boiling point: 82.3°C), etc., and the second organic solvent may be dimethyl sulfoxide (DMSO: 189°C), etc.
[0035] When the polymer for the porous layer is (iii) a fluororesin, examples of the first organic solvent include acetone (boiling point: 56°C), tetrahydrofuran (THF, boiling point: 66°C), etc., and examples of the second organic solvent include methyl ethyl ketone (MEK, boiling point: 79.6°C), N,N-dimethylacetamide (DMAc, boiling point: 165°C), dimethyl sulfoxide (DMSO, boiling point: 189°C), N,N-dimethylformamide (boiling point: 153°C), N-methyl-2-pyrrolidone (NMP, boiling point: 202°C), hexamethylphosphate triamide (boiling point: 232.5°C), etc.
[0036] When the polymer for the porous layer is (iv) polyamic acid (a precursor of polyimide), the first organic solvent may be, for example, N,N-dimethylacetamide (DMAc, boiling point: 165°C) or N-methyl-2-pyrrolidone (NMP, boiling point: 202°C), and the second organic solvent may be triethylene glycol dimethyl ether (triglyme, boiling point: 216°C) or tetraethylene glycol dimethyl ether (Tetraglyme, boiling point: 275°C).
[0037] When the polymer for the porous layer is (v) polysilazane (a precursor of silica glass), examples of the first organic solvent include benzene (boiling point: 80.1°C), 1,4-dioxane (boiling point: 101°C), toluene (boiling point: 110.6°C), dibutyl ether (DBE, boiling point: 142°C), and xylene (boiling point: 138°C to 144°C). Examples of the second organic solvent include amine-based solvents such as 2-diethylaminoethanol (boiling point: 162°C), dimethyloctylamine (boiling point: 195°C), and tetramethylhexanediamine (boiling point: 210°C). The amine-based solvent also acts as a catalyst for the hydrolysis (deammoniacation) of the polysilazane. From the viewpoint of more efficiently producing a stronger porous layer (porous silica glass layer), the ratio of the amine-based solvent to the polysilazane is preferably 1% to 10% by mass.
[0038] The ratio of the first organic solvent to the second organic solvent is not particularly limited, but for example, the ratio (V1 / V2) of the volume of the first organic solvent (V1) to the volume of the second significant solvent (V2) is preferably 50 / 50 or more, or 80 / 20 or more. The upper limit of the ratio (V1 / V2) is not particularly limited, but is preferably 999 / 1 or less, or 99 / 1 or less. When the ratio (V1 / V2) is within the above range, phase separation is promoted within the coated layer, and a porous layer can be efficiently produced. Also, the larger the value of the ratio (V1 / V2) (the lower the V2 ratio), the smaller the pore size of the porous layer tends to be, and the smaller the value of the ratio (V1 / V2) (the higher the V2 ratio), the larger the pore size of the porous layer tends to be. For this reason, the pore size of the porous layer can be adjusted to a desired size by adjusting the value of the ratio (V1 / V2). Furthermore, if the mixed solvent contains two or more first organic solvents, V1 is the total volume of all first organic solvents.
[0039] The mixed solvent may contain other solvents (e.g., water, a third organic solvent, etc.) different from the first and second organic solvents, as long as the effects of this embodiment are achieved. The total proportion of the first and second organic solvents in the mixed solvent may be 60% by volume or more, 70% by volume or more, 95% by volume or more, or 100% by volume.
[0040] The porous layer-forming composition may consist only of a mixed solvent and a porous layer polymer, or it may contain other components as needed (for example, known fillers contained in the resin described above). However, from the viewpoint of more efficiently producing a porous layer, it is preferable that it consists only of a mixed solvent and a porous layer polymer. The total ratio of the mixed solvent and the porous layer polymer in the porous layer-forming composition may be 95% by mass or more, or 100% by mass.
[0041] A porous layer-forming composition may be prepared by mixing a porous layer polymer, a mixed solvent, and other components as needed, using a known method. For example, a polymer solution A containing a porous layer polymer and a first organic solvent, and a polymer solution B containing a porous layer polymer and a second organic solvent may be prepared, and these two polymer solutions A and B may be mixed to obtain a porous layer-forming composition. Alternatively, a porous layer-forming composition may be prepared by adding the other solvent to a polymer solution C containing one of the first and second organic solvents and a porous layer polymer. The polymer solutions A to C used in composition preparation may be commercially available products. Examples of such commercially available products include polyamic acid solutions such as U-imide® varnish AR (NMP solution), CR (NMP solution), and BH (DMAc solution) manufactured by Unitika Ltd.
[0042] The first member forming the coating layer is not particularly limited, as long as it is desired to be joined with the second member. Examples of materials contained in the first member include the following: For example, glass such as silica glass; metals such as magnesium, aluminum, titanium, zirconium, chromium, iron, copper, nickel, zinc, silver, platinum, and gold; alloys such as stainless steel, Hastelloy, duralumin, brass, and magnesium alloys; metal oxides such as magnesium oxide, aluminum oxide, titanium oxide, and zirconium oxide; polyolefin resins such as polyethylene, polyethylene vinyl alcohol, and polypropylene; styrene-based resins such as polyvinyl alcohol, polyvinyl chloride, polyvinylidene fluoride, poly(meth)acrylic acid ester, polyacrylonitrile, polycarbonate, polystyrene, AS resin, and ABS resin; polyamide resins such as nylon; polyester resins such as polyethylene terephthalate and polybutylene terephthalate; polyimide resins; fluororesins; thermoplastic resins such as polyether ketone, polysulfone, polyoxymethylene, and polyphenylene sulfide; thermosetting resins such as epoxy resin, phenolic resin, urea resin, and melamine resin; ceramics; wood; and paper. The first component may consist solely of these materials, or it may contain known additives as needed, depending on the function and application of the first component, or the application of the composite product which is the final product.
[0043] The shape of the surface on which the coating layer of the first member is formed is not particularly limited; it may be a flat surface, a curved surface, or a surface with steps or other features. Furthermore, the surface condition is not particularly limited; it may be a non-porous flat surface, a surface with irregularities, or a porous surface.
[0044] From the viewpoint of obtaining high bonding strength (adhesion), it is preferable that the first member and the polymer for the porous layer have affinity. If the first member and the polymer for the porous layer have affinity, the bonding strength between the first member and the second member can be increased even if the surface of the first member is a non-porous flat surface. Examples of cases where affinity exists include when the first member contains the same type of polymer as the polymer for the porous layer, for example, in the following cases: when the polymer for the porous layer is polyamic acid (a precursor of polyimide) and the first member contains polyimide; or when the polymer for the porous layer is polysilazane (a precursor of silica glass) and the first member is silica glass.
[0045] Furthermore, the composite of this embodiment is not limited to the above-described combination of porous layer polymer and first member. Depending on the application of the composite, a very high bonding strength may not be required, and if the surface of the first member is a porous surface, a strong bonding (adhesion) strength can be obtained even with combinations other than those described above. Moreover, even with combinations other than those described above, using the porous layer forming composition of this embodiment allows for the bonding of the first member and the second member with sufficient (practical) bonding strength with a lower environmental impact and in a simple manner compared to conventional methods.
[0046] The method for applying the porous layer-forming composition to the surface of the first member is not particularly limited, and known methods can be used. For example, brush coating, spray coating, spin coating, dipping, squeegeeing, casting, inkjet methods, etc., may be used. The thickness of the coating layer may be adjusted as appropriate according to the desired thickness of the porous layer to be ultimately obtained.
[0047] <Process S2> At a temperature of 5°C or higher, the mixed solvent is vaporized and removed from the coated layer to form a porous layer (step S2 in Figure 1). As described above, the mixed solvent vaporizes from the coated layer in multiple steps (gradually from the low-boiling point solvent), and in this process, phase separation (drying-induced phase separation) occurs between the polymer for the porous layer and the solvent. As a result, a porous layer 70 can be formed on the first member 10, as shown in Figure 2(a). Thus, in this manufacturing method, a porous layer can be formed by a very simple method of applying the porous layer-forming composition to the first member and drying it (removal of the mixed solvent).
[0048] The porous layer formed is either a porous layer of the porous layer polymer in the coated layer, or a reaction product polymer of the porous layer polymer (precursor polymer). For example, if the porous layer polymer is (i) acrylic resin, (ii) vinyl copolymer of polyolefin resin, or (iii) fluororesin, then (i) an acrylic resin porous layer, (ii) a vinyl copolymer porous layer of polyolefin resin, and (iii) a fluororesin porous layer are obtained, respectively. Also, if the porous layer polymer is, for example, (iv) polyamic acid or (v) polysilazane, then (iv) a polyimide porous body and (v) a silica glass porous body are obtained, respectively. The porous layer may also contain unreacted precursor polymer along with the reaction product polymer of the precursor polymer, within the range that achieves the effects of this embodiment. For example, (iv) a polyimide porous body may contain polyamic acid, and (v) a silica glass porous body may contain polysilazane.
[0049] Unlike freeze-drying, the removal (vaporization) of the mixed solvent in this manufacturing method does not require low temperature and low pressure. Therefore, compared to freeze-drying, it is possible to reduce manufacturing costs and shorten manufacturing time.
[0050] The conditions for removing (vaporizing) the mixed solvent in this manufacturing method are not particularly limited except that it is carried out at 5°C or higher, and may be appropriately adjusted depending on the type of polymer for the porous layer, the mixed solvent, and the first component. The upper limit of the temperature is not particularly limited, but may be, for example, 200°C or lower, or 150°C or lower. Furthermore, the removal (vaporization) of the mixed solvent may be carried out at room temperature (normal temperature) without any special temperature control (for example, 5°C to 40°C, or 10°C to 30°C). Furthermore, the removal (vaporization) of the mixed solvent may be carried out at atmospheric pressure, for example, or while reducing the pressure to promote vaporization. Furthermore, the time required for the removal (vaporization) of the mixed solvent is not particularly limited, but may be, for example, 5 minutes or more, 30 minutes or more, or 60 minutes or more.
[0051] If the polymer for the porous layer is a precursor polymer, the precursor polymer is reacted in parallel with the vaporization of the mixed solvent to synthesize the polymer constituting the porous layer. For example, if the polymer for the porous layer is (iv) polyamic acid, polyimide is synthesized by imidation (dehydration and cyclization), and if the polymer for the porous layer is (v) polysilazane, hydrolysis (deammonia) occurs to synthesize silica glass. If the polymer for the porous layer is a precursor polymer, the mixed solvent may be removed (vaporized) while heating to promote the synthesis of the polymer constituting the porous layer. In this case, the temperature during removal (vaporization) of the mixed solvent may be, for example, 50°C to 200°C or 50°C to 150°C. The heating time is not particularly limited and may be adjusted as appropriate, but for example, it may be 5 minutes or more, 30 minutes or more, or 60 minutes or more.
[0052] The porous layer obtained by this manufacturing method is formed through phase separation of the porous layer polymer and solvent, followed by removal (vaporization) of the solvent, thus producing no residue. Furthermore, compared to methods using laser processing or pore-forming agents (pologens), it is easier to form complex porous structures (network-like, labyrinthine structures) from connecting pores, thereby exhibiting a strong anchoring effect. In addition, the pore size can be adjusted over a wide range by adjusting the mixed solvent ratio, etc.
[0053] The thickness of the porous layer is not particularly limited and may be adjusted as appropriate, but for example, it may be 50 nm to 100 μm, and from the viewpoint of obtaining higher bonding strength, 200 nm to 5 μm is preferred. The average pore diameter of the porous layer is not particularly limited and may be adjusted as appropriate, but for example, it may be 1 nm to 100 μm, and from the viewpoint of obtaining higher bonding strength, 20 nm to 3 μm is preferred. Here, the average pore diameter of the porous layer refers to the average diameter of the holes (openings) on the surface of the porous layer (the surface to which the second member is joined). The method for determining the average pore diameter of the porous layer is not particularly limited, but for example, it may be calculated by image analysis of a micrograph of the surface of the porous layer (AFM image, SEM image, etc.) (average pore diameter obtained by surface observation). For example, in a micrograph of the surface of the porous layer, 10 holes (openings on the surface) may be arbitrarily selected, and the average value of the circular diameter equivalent to the opening area of these holes may be used as the average pore diameter. Furthermore, if the porous layer has a complex network (maze-like) structure, for example, if the area occupied by voids exceeds 50% in a microscopic image of the surface of the porous layer, it may be classified as unmeasurable in terms of pore size measurement.
[0054] <Process S3> and <Process S4> A liquid composition is applied to the porous layer (step S3 in Figure 1), and the applied liquid composition is solidified to form a second member (step S4 in Figure 1). This yields a composite 100, as shown in Figure 2(b), which has a first member 10, a porous layer 70 formed on the surface of the first member 10, and a second member 20 formed on the porous layer 70.
[0055] The liquid composition may be, for example, (I) a solution of the organic polymer contained in the second component, or (II) a composition obtained by heating and softening or melting the second component.
[0056] The following describes an embodiment in which the liquid composition is (I) a solution of an organic polymer. The liquid composition (organic polymer solution) comprises a solvent and an organic polymer that dissolves in this solvent. Examples of organic polymers included in the second component are the following resins and copolymers thereof: acrylic resins, polyolefin resins, fluororesins, polyamic acid (a precursor of polyimide resins), polyvinyl alcohol, polyvinyl chloride, polyacrylonitrile, polycarbonate, polyvinyl acetate, styrene-based resins (e.g., polystyrene, AS resin, ABS resin, etc.), polyamide resins (e.g., nylon, etc.), polyester resins (e.g., polyethylene terephthalate, polybutylene terephthalate, etc.), polyether ketones, polysulfones, polyoxymethylene, polyphenylene sulfide, cellulose resins, epoxy resins, etc. Among these, thermoplastic polymers are preferred because they are easily soluble in the solvent. Furthermore, the second component may consist solely of an organic polymer, or it may contain known additives as necessary, depending on the function and application of the second component, or the application of the final composite product. Examples of known additives include colorants (dyes, pigments), fillers, spreaders, wetting agents, defoamers, dispersants, viscosity modifiers, wetting agents, heat stabilizers, UV stabilizers, rust inhibitors, and preservatives.
[0057] The solvent in the liquid composition (organic polymer solution) is not particularly limited as long as it is a solvent that dissolves the organic polymer, and can be appropriately selected based on the type of organic polymer. The concentration of the organic polymer in the liquid composition (organic polymer solution) is also not particularly limited and can be adjusted as appropriate, for example, it may be 1% to 30% by mass, or 3% to 20% by mass. Furthermore, the liquid composition (organic polymer solution) may consist only of the solvent and the organic polymer, or it may contain known additives that the second component may contain as needed. The method for producing the liquid composition (organic polymer solution) is not particularly limited, and for example, it may be produced by mixing the organic polymer, the solvent, and additives as needed by a known method. The method for applying the liquid composition (organic polymer solution) to the porous layer is also not particularly limited, and for example, the known method described in step S1 can be used.
[0058] At least a portion of the liquid composition (organic polymer solution) applied to the porous layer impregnates (penetrates) into the interior of the porous layer and then solidifies. The solidification of the liquid composition (organic polymer solution) is carried out by vaporizing and removing the solvent. The conditions for solidification of the liquid composition (vaporization of the solvent) are not particularly limited and may be carried out at room temperature and pressure (e.g., atmospheric pressure, 5°C to 40°C, or 10°C to 30°C). Heating, reduced pressure and / or pressurization may also be performed to promote solvent removal.
[0059] The following describes an embodiment in which the liquid composition is (II) a composition obtained by heating and softening or melting the second member. The second component preferably contains a thermoplastic polymer, as it is easily melted by heat. Examples of thermoplastic resins include the thermoplastic resins described in embodiment (I) above.
[0060] In embodiment (II), first, a second member containing an organic polymer (thermoplastic resin) is prepared. The second member may consist only of the organic polymer, or it may contain known additives as necessary depending on the function and application of the second member, or the application of the composite, which is the final product. Next, the second member is placed (laminated) on the porous layer and hot-pressed. As a result, the second member (thermoplastic resin) softens or melts into a liquid composition, and at least a portion of the liquid composition (molten or softened organic polymer) impregnates (penetrates) into the porous layer, and then cools and solidifies. The conditions for hot pressing are not particularly limited and may be adjusted as appropriate.
[0061] In both embodiments (I) and (II) described above, at least a portion of the liquid composition impregnates (penetrates) into the porous layer and then solidifies. As shown in Figure 2(b), in the porous layer 70, there is a region 20A on the interface side with the second member 20 where the second member 20 penetrates to fill the voids in the porous layer. The second member 20 is formed continuously from the inside of the porous layer 70, and the second member 20 can be strongly bonded to the porous layer 70. The second member 20 and the porous layer 70 are physically bonded (by the anchoring effect), so bonding is possible even if the chemical affinity is low.
[0062] Furthermore, steps S3 and S4 are not limited to the embodiments (I) and (II) described above. For example, the liquid composition may contain a precursor (monomer, oligomer, precursor polymer, etc.) of the organic polymer contained in the second member. The liquid composition containing the precursor may be applied to the porous layer, and after at least a portion of the liquid composition has impregnated (penetrated) into the porous layer, the precursor may be reacted by light irradiation or heating, etc., to solidify the liquid composition and form the second member. The liquid composition may optionally contain a crosslinking agent, a reaction initiator, etc. Alternatively, for example, the heat-meltable composition (molten resin) of the second member may be cast onto the porous layer, and after at least a portion of the heat-meltable composition has impregnated (penetrated) into the porous layer, it may be cooled and solidified to form the second member.
[0063] The use of the second member 20 shown in Figure 2(b) is not particularly limited. For example, the second member 20 may be a coating layer (paint film), a coating layer (coating film), etc., for the first member 10. In this case, the porous layer 70 functions as a base layer or primer layer for the second member 20.
[0064] <Variation> The second member 20 may serve as an adhesive layer. As a modified example of this embodiment, a composite 110 is shown in Figure 2(c). The composite 110 has a configuration in which a third member 30 is further bonded to the second member 20 of the composite 100 shown in Figure 2(b). The composite 110 has the same configuration as the composite 100 except for having the third member 30, and the preferred embodiment is also the same.
[0065] In the composite 110, the second member 20 functions as an adhesive layer, and the porous layer 70 functions as a base layer and primer layer for the adhesive layer (second member) 20. That is, the first member 10 and the third member 30 are joined via the base layer (porous layer) 70 and the adhesive layer (second member) 20. The material of the third member 30 is not particularly limited and can be the same as the material that the first member described above may contain. In this modified example, the range of choices for the combination of members to be joined (first member and third member) can be further broadened.
[0066] The method for manufacturing the composite 110 is not particularly limited, but for example, steps S1 to S3 are carried out in the same manner as the method for manufacturing the composite 100 described above (see Figure 1), and in step S4, the liquid composition (liquid adhesive layer) is solidified while the third member is in contact with the liquid composition. For example, in the embodiment where the liquid composition is (I) an organic polymer solution, the porous layer and the third member are brought into contact before the organic polymer solution on the porous layer solidifies (before the solvent vaporizes), and the organic polymer solution is solidified in that state. Alternatively, in the embodiment where the liquid composition is (II) a composition obtained by heating and softening or melting the second member, the second member (adhesive layer) and the third member are stacked on top of the porous layer formed on the first member in that order, and the third member is hot-pressed from above. The porous layer and the third member can be connected by the heat-melted second member (adhesive layer).
[0067] Furthermore, for example, if the liquid composition contains a precursor (monomer, etc.) of an organic polymer contained in the second member, the liquid composition may be applied to the porous layer, and the third member may be brought into contact with it, while the precursor is reacted by light irradiation or heating to solidify the liquid composition. Alternatively, for example, the heat-meltable composition (molten resin) of the second member may be cast onto the porous layer, and the heat-meltable composition (molten resin) may be cooled and solidified while the third member is brought into contact with it. [Examples]
[0068] The present invention will be further described using examples and comparative examples, but the scope of the present invention is not limited in any way by the examples and comparative examples.
[0069] [Preparation of samples for surface observation] The porous layer polymers, first organic solvent, second organic solvent, etc., used in Experiments 1-1 to 6-3 are summarized in Tables 1 to 4 below.
[0070] <Experiment 1-1> Acetone solution and (ethanol / water) solution of poly(methyl methacrylate) (PMMA) were prepared separately. The polymer (PMMA) concentration was the same in both solutions. These two solutions were mixed to obtain porous layer-forming composition 1-1 (hereinafter referred to as "composition" as appropriate). In composition 1-1, the PMMA concentration was 4% by mass, and the solvent ratio (by volume) was acetone / ethanol / water = 10 / 5 / 1.
[0071] Composition 1-1 was applied to a substrate (glass plate) using spin coating (1000 rpm, 60 seconds) to form a coating layer, and sample 1-1 was obtained by drying at atmospheric pressure and room temperature for 30 minutes.
[0072] <Experiment 1-2> An acetone solution of PMMA was prepared and designated as Composition 1-2. In Composition 1-2, the PMMA concentration was 4% by mass. Using Composition 1-2, Sample 1-2 was prepared in the same manner as in Experiment 1-1.
[0073] <Experiment 2-1> Solutions of polyvinyl alcohol / polyethylene copolymer (PVA-co-PE) in ethanol / water and dimethyl sulfoxide (DMSO) were prepared separately. The polymer concentration was the same in both solutions. Composition 2-1 was obtained by mixing these two solutions. In composition 2-1, the PVA-co-PE concentration was 4% by mass, and the solvent ratio (by volume) was ethanol / DMSO / water = 63 / 10 / 27. Sample 2-1 was prepared using composition 2-1 in the same manner as in experiment 1-1.
[0074] <Experiment 2-2> A DMSO solution of PVA-co-PE was prepared and designated as Composition 2-2. The PVA-co-PE concentration was 4% by mass. Using Composition 2-2, Sample 2-2 was prepared in the same manner as in Experiment 1-1.
[0075] <Experiment 3-1> ~ <Experiment 3-4> Acetone solution of (vinylidene fluoride / hexafluoropropylene) copolymer (P(VDF-HFP)) and an N-methyl-2-pyrrolidone (NMP) solution were prepared separately. The polymer concentration in both solutions was kept the same. Compositions 3-1 to 3-4 were obtained by mixing these two solutions. In compositions 3-1 to 3-4, the P(VDF-HFP) concentration was set to 3.5% by mass, and the solvent ratio (by volume), acetone / NMP, was adjusted to the values shown in Table 2. Samples 3-1 to 3-4 were prepared using compositions 3-1 to 3-4 in the same manner as in Experiment 1-1, except that the spin coating rotation speed was set to 2000 rpm.
[0076] <Experiment 3-5> An acetone solution and an aqueous solution of P(VDF-HFP) were prepared separately. The polymer concentration was the same in both solutions. Composition 3-5 was obtained by mixing these two solutions. In composition 3-5, the concentration of P(VDF-HFP) was 3.5% by mass, and the solvent ratio (by volume) was acetone / water = 9 / 1. Sample 3-5 was prepared using composition 3-5 in the same manner as in experiment 1-1.
[0077] <Experiment 4-1> ~ <Experiment 4-3> Acetone solutions and methyl ethyl ketone (MEK) solutions of (vinylidene fluoride / trifluoroethylene) copolymer (P(VDF-TrFE)) were prepared, respectively. The polymer concentration in both solutions was kept the same. Compositions 4-1 to 4-3 were obtained by mixing these two solutions. In compositions 4-1 to 4-3, the P(VDF-TrFE) concentration was set to 3.5% by mass, and the solvent ratio (by volume), acetone / MEK, was adjusted to the values shown in Table 2. Samples 4-1 to 4-3 were prepared using compositions 4-1 to 4-3 in the same manner as in Experiment 1-1.
[0078] <Experiment 5-1> First, a polyimide precursor polyamic acid NMP solution (manufactured by Unitika Ltd., U-imide® varnish AR, polyamic acid concentration: 18% by mass) was diluted with NMP to prepare a diluted solution (polyamic acid concentration: 14.4% by mass). Composition 5-1 was prepared by mixing the diluted solution with tetraethylene glycol dimethyl ether (Tetraglyme) in a mass ratio (diluted solution):(Tetraglyme)=80:20. In composition 5-1, the polyamic acid concentration was 11.5% by mass, and the solvent ratio (by volume) was NMP / Tetraglyme=77 / 23.
[0079] Using composition 5-1, a coating layer was formed on a substrate (glass plate) in the same manner as in experiment 1-1, and the mixture was heated at 150°C for 30 minutes to obtain sample 5-1.
[0080] <Experiment 5-2> ~ <Experiment 5-4> First, a solution of polyamic acid, a polyimide precursor, in N,N-dimethylacetamide (DMAc) (manufactured by Unitika Ltd., U-imide® varnish BH, polyamic acid concentration: 26% by mass) was diluted with NMP to prepare a diluted solution (polyamic acid concentration: 14.4% by mass). Compositions 5-2 to 5-4 were prepared by mixing the diluted solution with Tetraglyme in mass ratios (diluted solution):(Tetraglyme) = 80:20, 60:40, and 95:5, respectively. The polyamic acid concentration and solvent ratio (by volume) for each composition are as follows. Composition 5-2 (Polyamic acid concentration: 11.5% by mass, (DMAc+NMP) / Tetraglyme=77 / 23), Composition 5-3 (Polyamic acid concentration: 8.6% by mass, (D MAc+NMP) / Tetraglyme=56 / 44), composition 5-4 (polyamic acid concentration: 13.7% by mass, (DMAc+NMP) / Tetraglyme=94 / 6).
[0081] Samples 5-2 to 5-4 were prepared using compositions 5-2 to 5-4 in the same manner as in Experiment 5-1.
[0082] <Experiment 6-1> ~ <Experiment 6-3> Compositions 6-1 to 6-3 were prepared by adding amines 1 to 3, as shown in Table 4, to a dibutyl ether (DBE) solution of perhydropolysilazane (PHPS), a silica glass precursor. In each composition, the PHPS concentration and solvent ratio (by volume) were as follows: Composition 6-1 (PHPS: 19.8% by mass, DBE / amine 1 = 79.2 / 1.0), Composition 6-2 (PHPS: 19.8% by mass, DBE / amine 2 = 79.2 / 1.0), Composition 6-3 (PHPS: 19.8% by mass, DBE / amine 3 = 79.2 / 1.0).
[0083] Using compositions 6-1 to 6-3, coating layers were formed on a substrate (glass plate) in the same manner as in Experiment 1-1. Each coating layer was heated and dried under the following conditions to obtain samples 6-1 to 6-3: Experiment 6-1: heated at 70°C for 60 minutes, Experiment 6-2: heated at 70°C for 60 minutes, Experiment 6-3: heated at 140°C for 60 minutes.
[0084] Of the compositions prepared in Experiments 1-1 to 6-3 described above, P (VDF-HFP) did not completely dissolve in the mixed solvent (volume ratio: acetone / water = 90 / 10) in composition 3-5. In compositions other than composition 3-5, the polymer dissolved completely in the solvent.
[0085] [Table 1]
[0086] [Table 2]
[0087] [Table 3]
[0088] [Table 4]
[0089] [Surface observation] Surface observations were performed on the prepared samples using an atomic force microscope (AFM). The results are shown in Figures 3 to 9.
[0090] Figures 3(a)-(b) and 4(a)-(b) show the AFM images of samples 1-1 and 1-2, and samples 2-1 and 2-2, respectively. As shown in Figure 3(a), in Experiment 1-1, where two types of organic solvents (acetone (boiling point 56°C) / ethanol (boiling point 78.4°C)) were used as the solvent for the composition, a PMMA porous layer (sample 1-1) was obtained. On the other hand, as shown in Figure 3(b), in Experiment 1-2, where only acetone was used as the solvent for the composition, the PMMA layer obtained (sample 1-2) showed almost no pores on the surface. Furthermore, as shown in Figure 4(a), in Experiment 2-1, which used two types of solvents (ethanol (boiling point 78.4°C) / DMSO (189°C)) as the solvent for the composition, a network-like PVA-co-PE porous layer (sample 2-1) with complexly formed connecting pores was obtained. On the other hand, as shown in Figure 4(b), the PVA-co-PE layer (sample 2-2) obtained in Experiment 2-2, which used only DMSO as the solvent for the composition, showed only slight surface irregularities.
[0091] Figures 5(a) to (d) show AFM images of samples 3-1 to 3-4 (P(VDF-HFP) porous layer), respectively. In samples 3-1 to 3-4, where the organic solvent ratio of the composition (by volume, acetone (boiling point 56°C) / NMP (boiling point 202°C)) was varied, the pore size increased as the ratio (acetone / NMP) decreased (as the NMP ratio increased). Ten pores (openings on the surface) were arbitrarily selected from the AFM images in Figures 5(a) to (d), and the average pore size was calculated by image analysis using the average value of the diameter of a circle equivalent to the opening area of these pores. The results are as follows: Sample 3-1: 0.635 μm, Sample 3-2: 1.00 μm, Sample 3-3: 2.05 μm, Sample 3-4: A complex network of interconnected pores; pore size could not be determined.
[0092] Figure 6(a) shows an AFM image of sample 3-5, and Figure 6(b) shows an optical microscope image of sample 3-5 (a wide-area image of Figure 6(a)). The composition of experiment 3-5 contained only one type of organic solvent, acetone, and as mentioned above, P(VDF-HFP) was not completely dissolved in the mixed solvent (acetone / water). Sample 3-5, prepared using such an unstable composition, did not yield a uniform layer, and clumps of P(VDF-HFP) were present (white areas in Figure 6(a), black areas in Figure 6(b)), and no pores were observed on the surface.
[0093] Figures 7(a) to 7(c) show AFM images of samples 4-1 to 4-3 (P(VDF-TrFE) porous layer), respectively. As can be seen from Figures 7(a) to 7(c), in samples 4-1 to 4-3, in which the organic solvent ratio of the composition (by volume, acetone (boiling point 56°C) / MEK (boiling point 79.6°C)) was varied, the pore size increased as the ratio (acetone / MEK) decreased (as the MEK ratio increased).
[0094] Figures 8(a) to 8(d) show AFM images of samples 5-1 to 5-4, respectively. As shown in Figures 8(a) to 8(d), in experiment 5-1, which used two types of organic solvents (NMP (boiling point 202°C) / Tetraglyme (275°C)) as the solvent of the composition, and in experiments 5-2 to 5-4, which used three types of organic solvents (DMAc (165°C), NMP / Tetraglyme), porous layers of polyimide in which polyamic acid was imidized (dehydrated and cyclized) were obtained (samples 5-2 to 5-4). Furthermore, comparing sample 5-2 and sample 5-3, sample 5-3, which had a smaller organic solvent ratio (by volume, total amount of DMAc and NMP / Tetraglyme) (higher Tetraglyme ratio), showed larger pore sizes. On the other hand, sample 5-4, which had a larger organic solvent ratio (by volume, total amount of DMAc and NMP / Tetraglyme) (lower Tetraglyme ratio), formed a porous layer with very small particle sizes (nano-order).
[0095] Figures 9(a) to 9(c) show AFM images of samples 6-1 to 6-3, respectively. As shown in Figures 9(a) to 9(c), in experiments 6-1 to 6-3, which used two types of organic solvents (DBE (boiling point 142°C) / amine (boiling point 162°C to 210°C)) as solvents for the composition, porous layers of silica glass obtained by hydrolysis of PHPS (samples 6-1 to 6-3) were obtained.
[0096] [Fabrication of composite members (composites) and evaluation of bonding strength] <Experiment 7> (i) Preparation of sample 7 As sample 7, a composite member was manufactured by joining a glass plate (first member) and a second member (styrene-ethylene-butylene-styrene block copolymer (SEBS)) via a P(VDF-TrFE) porous layer.
[0097] Acetone solution and NMP solution of P(VDF-TrFE) were prepared separately. The polymer concentration was the same in both solutions. Composition 7 for forming a porous layer was obtained by mixing these two solutions. In composition 7, the concentration of P(VDF-TrFE) was 3.5% by mass, and the solvent ratio (by volume) was acetone / NMP = 99 / 1.
[0098] As the first component, a glass plate (soda-lime glass (blue plate), 50 mm wide x 50 mm wide, 5 mm thick) was prepared. Composition 7 was applied to the first component using spin coating to form a coating layer, and the plate was dried at atmospheric pressure and room temperature for 5 minutes to form a porous layer 7.
[0099] As a liquid composition for forming the second component, an SEBS solution (manufactured by Asahi Kasei Corporation, ToughTec® H1052, solvent: chlorobenzene, SEBS concentration: 7% by mass) was prepared. The liquid composition was applied to the porous layer and heated at 150°C for 5 minutes to form the second component, obtaining sample 7.
[0100] (ii) SEM observation and measurement of the thickness of the porous layer SEM observation was performed on sample 7. Figure 10(a) shows a cross-sectional SEM image of sample 7 in the state where a P(VDF-TrFE) porous layer was formed on a glass plate during the fabrication process. Figure 10(b) shows a cross-sectional SEM image of the completed sample 7 (a composite in which a glass plate and an SEBS member are connected by a P(VDF-TrFE) porous layer). In Figure 10, "glass" refers to the glass plate, "PVDF" refers to the P(VDF-TrFE) porous layer, and "SEBS" refers to the SEBS member.
[0101] A sample for measuring film thickness was measured using composition 7 under the same conditions as sample 7 described above. However, in the sample for measuring film thickness, a portion of the coating layer was removed from the glass plate before it hardened (dried), creating a step on the glass plate (a step between the area with and without the porous layer). AFM measurement was performed on the sample for measuring film thickness, and the film thickness of the porous layer was calculated. The film thickness of the porous layer was approximately 1 μm.
[0102] (iii) Measurement of tensile strength As a comparative sample to sample 7, a composite member was manufactured by joining a glass plate (first member) and a second member (SEBS) via a non-porous layer of P(VDF-TrFE). The comparative sample was prepared in the same manner as sample 7, except that the non-porous layer was formed using an NMP solution of P(VDF-TrFE) (resin concentration: 3.5% by mass) instead of composition 7.
[0103] A φ20 mm dolly (a gripping device for measurement) was attached to the second member of sample 7 and the comparison sample using epoxy adhesive, with a load of 500 g applied. Using a pull-off type automatic adhesion tester (PosiTest AT-A, manufactured by Cortec Co., Ltd.), tensile tests were performed in the lamination direction (perpendicular to the connection surface) of sample 7 and the comparison sample in accordance with JIS K 5600-5-7 to evaluate the joint strength of the first and second members in the perpendicular direction. Specifically, tensile tests were performed using the dolly at 1 MPa / second. The results are shown in Figure 11.
[0104] In Figure 11, the vertical axis represents the stress applied to the sample, and the horizontal axis represents the elapsed time from the start of the tensile test. As shown in Figure 11, it was confirmed that sample 7, which has a porous layer, has a higher bonding strength (maximum tension) compared to the comparison sample.
[0105] <Experiment 8> (i) Preparation of sample 8 As sample 8, a composite member was manufactured by joining glass plates (first members) 11a and 11b and a second member (PMMA) 12 via silica glass porous layers 13a and 13b, as shown in Figure 12(a).
[0106] Composition 8 was prepared by adding dimethyloctylamine (amine 1) to a dibutyl ether (DBE) solution of PHPS, a silica glass precursor. In composition 8, the PHPS concentration was 19.8% by mass, and the solvent ratio (by volume) was DBE / amine 1 = 79.2 / 1.0.
[0107] Two glass plates (float glass, 100 mm wide x 25 mm thick, 2 mm thick) 11a and 11b were prepared as the first components. Composition 8 was applied to the 12.5 mm x 25 mm area at the end of each first component to form a coating layer, and the plate was heated at 70°C for 10 minutes to form porous layers 13a and 13b.
[0108] A PMMA solution (solvent: acetone, PMMA concentration: 15% by mass) was prepared as a liquid composition for forming the second member. The liquid composition was applied to one of the two porous layers, porous layer 13a, and the other porous layer 13b was placed on top and temporarily fixed in place. A 500g weight was then placed on top and allowed to air dry to form the second member, obtaining sample 8.
[0109] (ii) Measurement of the thickness of the porous layer A sample for measuring film thickness was measured using composition 8 under the same conditions as sample 8 described above. However, in the sample for measuring film thickness, a portion of the coating layer was removed from the glass plate before it hardened, creating a step on the glass plate (a step between the area with and without the porous layer). AFM measurement was performed on the sample for measuring film thickness, and the film thickness of the porous layer was calculated. The film thickness of the porous layer was approximately 210 nm.
[0110] (iii) Measurement of shear strength As a comparative sample to sample 8, a composite member was manufactured by directly joining a glass plate (first member) and a second member (PMMA). The comparative sample was made by bonding two glass plates with PMMA. The comparative sample has the same configuration as sample 8 shown in Figure 12(a), except that it does not have silica glass porous layers 13a and 13b.
[0111] Using a benchtop precision universal testing machine (Shimadzu Corporation, AGS-X 10kN), shear tests were performed on sample 8 and a comparison sample in the horizontal direction (parallel to the connecting surface) in accordance with JIS K 6850:1999 to evaluate the horizontal joint strength (shear force) of the first and second members. The tensile speed was set to 1 mm / min, and three different test pieces were measured. The result showing the median value of the fracture strength was adopted. The results are shown in Figure 12(b).
[0112] In Figure 12(b), the vertical axis represents the force applied to the sample, and the horizontal axis represents the displacement. As shown in Figure 12(b), it was confirmed that sample 8, which has a porous layer, has a higher bonding strength compared to the comparative sample. [Industrial applicability]
[0113] In the manufacturing method of this embodiment, even if the first and second members are made of dissimilar materials that are difficult to join together, a strong bond can be formed to produce a composite. For this reason, the composite manufactured in this embodiment is expected to be used in a wide range of fields, such as automotive parts, electronics, building materials, and optical instruments. [Explanation of symbols]
[0114] 10 First member, 20 Second member porous layer, 20A Region where the second member penetrates to fill the voids in the porous layer, 30 Third member, 70 Porous layer, 100,110 Composite, 8 Sample 8, 11a,11b Glass plate (first member), 12 PMMA (second member), 13a,13b Silica glass porous layer
Claims
1. A method for manufacturing a composite including a joined first member and a second member, A porous layer-forming composition is applied to the surface of the first member to form a coating layer, By vaporizing and removing the mixed solvent from the coating layer at a temperature of 5°C or higher, a porous layer is formed. Applying a liquid composition onto the porous layer, The process includes solidifying the liquid composition to form a second member, The porous layer forming composition is The mixed solvent containing two or more organic solvents, The mixture includes a polymer for porous layers dissolved in the aforementioned mixed solvent, The mixed solvent is Of the aforementioned organic solvents, the second organic solvent with the highest boiling point, A method for producing a composite, comprising a first organic solvent having a boiling point 20°C to 150°C lower than the boiling point of a second organic solvent.
2. The method for producing the composite according to claim 1, wherein the concentration of the porous layer polymer in the porous layer forming composition is 1% by mass to 35% by mass.
3. In the porous layer forming composition, A method for producing a composite according to claim 1, wherein the ratio (V1 / V2) of the volume of the first organic solvent (V1) to the volume of the second organic solvent (V2) is 50 / 50 or more.
4. The method for producing the composite according to claim 1, wherein the polymer for the porous layer comprises at least one selected from the group consisting of acrylic resin, vinyl copolymer of polyolefin resin, fluororesin, polyamic acid, and polysilazane.
5. A method for producing a composite according to claim 1, wherein a phase separation occurs between the porous layer polymer and the mixed solvent during the process of vaporizing and removing the mixed solvent from the coated layer.
6. The method for producing a composite according to claim 1, wherein, by applying the liquid composition, at least a portion of the liquid composition impregnates the porous layer, and the second member is formed continuously from the inside of the porous layer.
7. It is a complex, First member and A porous layer formed on the surface of the first member, It comprises a second member formed on the porous layer, The second member is a composite in which a portion of it penetrates the porous layer and is formed continuously from the inside of the porous layer.
8. A porous layer forming composition used for joining a first member and a second member, A mixed solvent containing two or more organic solvents, The mixture contains a polymer for porous layers dissolved in the aforementioned mixed solvent, The mixed solvent is Of the aforementioned organic solvents, the second organic solvent with the highest boiling point, A composition for forming a porous layer, comprising a first organic solvent having a boiling point 20°C to 150°C lower than the boiling point of a second organic solvent.
9. A porous layer that joins the first member and the second member, It comprises at least one selected from the group consisting of acrylic resin, vinyl copolymer of polyolefin resin, fluororesin, polyimide, and silica glass. The thickness is 50 nm to 100 μm. A porous layer with an average pore diameter of 1 nm to 100 μm or less.
Citation Information
Patent Citations
Substrate composite and manufacturing method thereof
JP6918341B2